2012
DOI: 10.1021/cb3003557
|View full text |Cite
|
Sign up to set email alerts
|

A Short DNA Aptamer That Recognizes TNFα and Blocks Its Activity in Vitro

Abstract: Tumor necrosis factor-alpha (TNFα) is a pivotal component of the cytokine network linked to inflammatory diseases. Protein-based, TNFα inhibitors have proven to be clinically valuable. Here, we report the identification of short, single-stranded DNA aptamers that bind specifically to human TNFα. One such 25-base long aptamer, termed VR11, was shown to inhibit TNFα signaling as measured using NF-κB luciferase reporter assays. This aptamer bound specifically to TNFα with a dissociation constant of 7.0 ± 2.1 nM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 51 publications
3
57
2
Order By: Relevance
“…The vast majority of aptamer applications have involved using the aptamer as a substitute for an antibody in an immunoassay-type platform although a few interesting exceptions exist using electrochemical-based detection platforms and others including aptamer-labeled pores [138, 139]. Reported aptamers that bind cytokines include: interferon-γ (IFN-γ) [140]; interleukin-6 (IL-6) [141]; IL-17 [142]; IL-32 [143]; oncostatin M, a member of the IL-6 family [144]; platelet derived growth factor (PDGF) [145]; tumor necrosis factor-α [146, 147], and vascular endothelial growth factor (VEGF) [148]. Among these cytokines, new analytical chemistry assays or devices have been described using aptamers against IFN-γ, PDGF and VEGF.…”
Section: Aptamer Assaysmentioning
confidence: 99%
“…The vast majority of aptamer applications have involved using the aptamer as a substitute for an antibody in an immunoassay-type platform although a few interesting exceptions exist using electrochemical-based detection platforms and others including aptamer-labeled pores [138, 139]. Reported aptamers that bind cytokines include: interferon-γ (IFN-γ) [140]; interleukin-6 (IL-6) [141]; IL-17 [142]; IL-32 [143]; oncostatin M, a member of the IL-6 family [144]; platelet derived growth factor (PDGF) [145]; tumor necrosis factor-α [146, 147], and vascular endothelial growth factor (VEGF) [148]. Among these cytokines, new analytical chemistry assays or devices have been described using aptamers against IFN-γ, PDGF and VEGF.…”
Section: Aptamer Assaysmentioning
confidence: 99%
“…We have recently shown that functional DNA aptamers targeting TNF-α 42 and CEA, 43 do not trigger cytokine responses linked to innate immunity. Consistently, the PEGylated aptamers used in this study did not activate a TLR9 innate immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Target-specific, short, single-stranded DNA (ssDNA) molecules, called aptamers, are auspicious ligands for numerous in vivo applications. [1][2][3][4] Using the combinatorial chemistry process SELEX (Systematic Evolution of Ligands by EXponential enrichment), aptamers can be selected from a large combinatorial pool of sequences, called start library, against various target molecules such as toxins, [5] antibiotics, [6] amino acids, [7] peptides, [8] proteins, [9] or whole living cells. [10][11][12] During the in vivo application, synthetic oligonucleotides come in contact with the cells of the patient's immune system.…”
Section: Introductionmentioning
confidence: 99%